Sterile hepatic abscess due to umbilical venous catheterization - Bayhan, Cihangül; Takcı, Şahin; Ciftçi, Türkmen Turan; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2012)
A preterm infant with isolated fetal ascites was admitted to the neonatal intensive care unit due to the appearance of respiratory distress at birth. An umbilical venous catheter (UVC) was inserted. Abdominal ultrasonography (US) showed localization of the catheter tip in the portal vein. It was removed and replaced with a newer one. UVC tip location was confirmed with X-ray. His condition had been improving until he worsened suddenly on the sixth day of life. US showed hepatic abscess and intraabdominal hemorrhage derived from the malpositioned UVC. A drainage catheter was inserted to the abscess and paracentesis was applied. Practitioners should be cautious about any signs of UVC complications, even if true localization of the catheter tip is proven at the first application. Furthermore, if it is difficult to decide whether the catheter tip is in the right location, confirmation with US can be considered.